The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jwas.12749
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sour lemon (Citrus limon) peel essential oil supplementation for reduction of deltamethrin‐induced stress in rainbow trout (Oncorhynchus mykiss)

Abstract: The purpose of this study was to investigate the dietary effects of using essential oil from sour lemon peel (Citrus limon) on growth performance, carcass composition, blood and serum parameters, and liver enzymes of juvenile rainbow trout (Oncorhynchus mykiss) exposed to deltamethrin (DMN) pesticide. Treatments with no lemon peel essential oil (LPEO) and without DMN (control), as well as four treatments with 10% of 96‐h lethal concentration of DMN were prepared with dietary supplementation of LPEO (zero, 200,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 92 publications
(99 reference statements)
1
2
0
Order By: Relevance
“…Pesticideinduced stress in fish and following increases in cortisol and glucose have been reported in many studies [85][86][87]. The current results were in line with previous studies that have reported the mitigating effect of herbs on stress caused by pesticides [13,16,88,89]. In probiotic treatments, the cortisol levels decreased only in the treatment 1 × 10 8 CFC/ g probiotic after exposure to the pesticide, which may return to the mitigating impacts of probiotics on stress [90,91].…”
Section: Aquaculture Nutritionsupporting
confidence: 92%
“…Pesticideinduced stress in fish and following increases in cortisol and glucose have been reported in many studies [85][86][87]. The current results were in line with previous studies that have reported the mitigating effect of herbs on stress caused by pesticides [13,16,88,89]. In probiotic treatments, the cortisol levels decreased only in the treatment 1 × 10 8 CFC/ g probiotic after exposure to the pesticide, which may return to the mitigating impacts of probiotics on stress [90,91].…”
Section: Aquaculture Nutritionsupporting
confidence: 92%
“…The EO of Citrus lemon was also tested in the study: inhibitory results were not as good; however, lemon EO has shown antibiofilm-forming properties in previous studies on food matrices [ 10 ]. Additionally, in aquaculture, the supplementation of the diets of rainbow trout with lemon EO [ 11 ], as well as the combination of 3% orange EO and 1% lemon EO in the diet of farmed fish, improved their health status [ 12 ]. In addition, citrus flavors are common in fish seasonings, so their incorporation into fish products may be highly accepted by consumers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…parameters in rainbow trout. In addition, dietary supplementation of sour lemon (Citrus Limon) peel essential oil alleviated the harmful outcomes of stress induced by deltamethrin (Amiri Resketi et al, 2021) in rainbow trout. In other research published by Mora-Sánchez et al (2020), adding Biocitro ® to the rainbow trout diet markedly improved disease resistance against Lactococcus garvieae.…”
mentioning
confidence: 99%